The Influence of Morality, Religiosity, and Employee Integrity on Financial Management Fraud in the Labuhan Batu Regency Government - Nabila Rizki Erjani; Nurlaila Nurlaila; Isnaini Harahap (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2026)
Background – The increasing prevalence of fraud cases in various government institutions, including the embezzlement of shop rental funds, cooking oil corruption, and bribery in the P3K recruitment process, indicates that fraud remains a serious issue that threatens the integrity of pubFlic institutions. Aim – The aim of this research is to empirically investigate the influence of morality, religiosity, and employee integrity on financial management fraud within the Government of Labuhan Batu Regency. Design / methodology / approach – This study involved 60 employees of the Labuhan Batu Regency Government. Data were collected through questionnaires and analyzed using classical assumption tests, hypothesis testing, and multiple regression analysis. Findings – The results show that morality, religiosity, and employee integrity each have a significant effect on financial management fraud. Higher levels of morality, religiosity, and integrity are associated with a lower tendency to engage in fraudulent behavior. Simultaneous testing confirms that these three variables jointly influence financial management fraud. Conclusion - Organizations are encouraged to strengthen ethical awareness by promoting moral values, reinforcing religiosity, and cultivating employee integrity to minimize the risk of financial management fraud Research implication – These findings indicate that morality, religiosity, and employee integrity play a crucial role in influencing the occurrence of fraud in government financial management. Limitations – This study is limited by its small sample size and narrow scope, as it only involves respondents from a single institution, namely the Government of Labuhan Batu Regency. Consequently, the findings may have limited generalizability to other government institutions with different organizational characteristics.